دراسة معرفية – تدولية لفلسفة وجود الله للفيلسوف الوجودي الملحد مارتن هايدجر : دراسة معرفية – تداولية لفلسفة وجود الله للفيلسوف الوجودي الملحد مارتن هايدجر - طيبة محمد موات; Prof. Dr. Hashim Aliwy Mohammed Alhusseini (Journal of College of Education, 2023)
Existentialism is a philosophical school that has man as its central theme. Influential circumstances that happened at that time brought about some changes in people's minds, thoughts and beliefs. People became hopeless, felt lost and lost confidence in everything, even their faith in God, and out of these changes came the idea of existentialism. This article presents a cognitive-pragmatic analysis of the philosophy of God's existence as expounded by the famous atheist existential philosopher Martin Heidegger. Heidegger's unique perspective offers a thought-provoking exploration of the interplay between cognition, pragmatics and human existence in relation to the concept of God. The study aims to explore Heidegger's arguments and highlight the cognitive processes involved as well as the pragmatic implications of his atheistic philosophical framework. Drawing on cognitive and pragmatic theories, the study examines the cognitive processes underlying the conceptualization of God. It explores how language, context and social conventions shape our understanding of the divine, and examines Heidegger's unique perspective on the pragmatic aspects of religious discourse. Using Lakoff and Johnson's (1980) Conceptual Metaphor Theory and Searle's (1975) classification of speech acts as a model of analysis for cognitive and pragmatic analysis respectively, the researchers selected three excerpts to demonstrate